Plasmodium falciparum: the human agglutinating antibody response to the infected red cell surface is predominantly variant specific. - Newbold, C; Pinches, R; Roberts, D; Marsh, K (1992)
There is mounting evidence that an important component of the host-protective immune response to Plasmodium falciparum is the antibody response to the altered surface of the infected erythrocyte. The nature of these surface changes and the responses to them have been difficult to analyse because of the diverse nature of the parasite-derived neoantigens (PDN) expressed, because of the additional presence of modified host determinants, and because of the lack of monospecific reagents. We have studied the reactivity of field isolates and laboratory clones with pooled or individual sera using a novel approach which obviates the need for specific antibody. We see marked diversity in PDN but in contrast to previous studies, we also find that the predominant agglutinating antibody response in humans is variant specific. Antibodies which cross-react between different serotypes are rare and react only with a subset of PDN types. These results have implications for mechanisms underlying the development of acquired immunity to P. falciparum.